Cost-effectiveness analysis of first-line pembrolizumab treatment for PD-L1 positive, non-small cell lung cancer in China. (3rd April 2019) - Liao, Weiting; Huang, Jiaxing; Hutton, David; Li, Qiu
Abstract: Purpose: Pembrolizumab was recently approved in several countries as a first-line treatment for patients with PD-L1 positive, non-small cell lung cancer (NSCLC). However, it is expensive. This study aimed to assess the cost-effectiveness of pembrolizumab in treating advanced NSCLC patients with PD-L1 positive cancer in China. Methods: A Markov model was developed to compare the cost-effectiveness of pembrolizumab with chemotherapy for patients with PD-L1 expression on at least 50% of NSCLC tumor cells. Model inputs for transition probabilities and toxicity were derived from published clinical trial data, while health utilities were estimated from a literature review. Costs for drugs were updated to standard fee data from West China Hospital in 2017. Health outcomes were measured in quality-adjusted life years (QALYs), and cost-effectiveness was measured as the incremental cost-effectiveness ratio (ICER). Sensitivity analyses were conducted to test the robustness of the model. Results: Pembrolizumab gained 0.45 QALYs at an incremental cost of $46, 362 compared to chemotherapy for an ICER of $103, 128 per QALY gained. In most scenarios, the ICER exceeded three times the Chinese Gross Domestic Product per capita. Two-way sensitivity analysis showed that, when the utility of the progression-free status increased to the maximal value of 0.845 and the 1 mg dose price decreased to $10.50, the ICER reduced to $25, 216/QALY. Conclusions: Pembrolizumab is not likely to be cost-effective in the treatment of PD-L1 positive, NSCLC for Chinese patients. Less aggressive pricing may increase accessibility for patients in China.